investment in the residential sector and its finacing - حامد, م.د.سهى مصطفى; عبدالجليل, م.د.عقيل عبدالله (Journal of Planner and Development, 2011)
Adopting a policy of attracting investments in all countries, whether developing or developed prevailed, especially after the global crisis, and this trend is imposed by considerations of political and development (urban, economic, and social) can be formulated as a rational policy to solve many problems related to patterns of urban growth, economic, social, and including the problem of housing. As the reality of the housing sector in Iraq will require the allocation of substantial resources to promote it by the research problem is the lack of financial resources and the inability of investments to meet the various requirements including the requirements of economic sectors, particularly in the field of housing, infrastructure and basic services associated with it in Iraq.